Working with Space and Shape in Early Childhood Education: Experiences in Collaboration - Fernandes, Karina Luiza da Silva; Megid, Maria Auxiliadora Bueno Andrade; Almeida, Alessandra Rodrigues de; Ferreira, Gislaine Cristina Bonalumi (Revista Eletrônica de Educação, 2016)
This report shows the experience of a work conducted with the Meli-Melo puzzle in two early childhood education classes at two different schools in the state of São Paulo, Brazil. With the work’s activities as a starting point, aspects related to space and shape, as well as quantities and measures, were approached. Children from two and a half to five years old participated in the playful activities, which had the following goals: to develop spatial and geometric skills, to allow measuring actions, to favor dialogue and to boost group work experience. There were several activities, like handling the pieces, assembling images freely or according with outlines and models, assembling three-dimensional figures, and the length game. The following questions were considered in the evaluation of the work: how was the children’s participation in large groups and small groups? How did children of different age groups engage in the different proposals? Which activities were easier or more difficult for each group? Which behaviors and conversations showed us new knowledge? The fulfillment of the planned activities showed that the children had several hypotheses regarding shapes and that they were able to identify similarities and differences, use geometry vocabulary, and discuss their thoughts, particularly when working in small groups, which favored the participation of nearly all children. We believe the work reported has allowed learnings and a contact with mathematics in early childhood education. Keywords: Early childhood education, learning mathematics, puzzles. O trabalho com espaço e forma na educação infantil: Experiências em colaboração Resumo Este relato apresenta a experiência de um trabalho com o quebra-cabeça “Meli-Melô” em duas turmas de educação infantil em Unidades Educacionais do interior de São Paulo, Brasil. A partir das atividades, trabalhamos aspectos relativos a espaço e forma e grandezas e medidas. As propostas de caráter lúdico foram realizadas com crianças de dois anos e meio a cinco anos, tendo como objetivos: desenvolver habilidades espaciais e geométricas, possibilitar a realização de ações de medir, favorecer o diálogo e promover a vivência de trabalho em grupo. Foram realizadas diferentes atividades como: manipulação das peças, montagem de figuras livremente e a partir de traçados e de sombras, montagem de figuras tridimensionais e jogo do comprimento. A avaliação do trabalho considerou a observação de algumas questões: como foi a participação das crianças no grupo grande e em pequenos grupos? Como as crianças, de diferentes faixas etárias participaram das diferentes propostas? Quais atividades foram mais fáceis ou mais difíceis para cada grupo? Quais comportamentos e falas nos revelaram aprendizagens? A realização das atividades planejadas demonstrou que as crianças têm diversas hipóteses acerca das formas, identificam semelhanças e diferenças, utilizam vocabulário geométrico, argumentam acerca do que pensam, especialmente no trabalho em pequenos grupos, cujas experiências favorecem a participação de quase todas as crianças que os compõem. Considera-se que o trabalho possibilitou aprendizagens e favoreceu o contato com a matemática na educação infantil. Palavras-chave: Educação Infantil. Aprendizagens em Matemática. Quebra-cabeças.